Population biology of the burrowing crab Neohelice granulata, (Crustacea: Decapoda: Varunidae) from a tropical mangrove in Brazil - Gregati, Rafael A. [UNESP]; Negreiros-Fransozo, Maria L. [UNESP] (Sociedade Brasileira de Zoologia, 2009)
The population biology of the burrowing crab Neohelice granulata (Dana, 1851) from a mangrove in Jabaquara Beach, Paraty, state of Rio de Janeiro, Brazil (23º13'04S and 44º42'47W), was studied with respect to the following traits: size-frequency distribution, recruitment, reproductive period, fecundity, and sex ratio. Specimens were sampled monthly from April, 2003 to March, 2004, at the river margins during low tide periods. Size, sex, presence of eggs, and stage of the female gonad were recorded. Ovigerous females had their eggs removed and counted. The reproductive period was continuous and the highest frequency of ovigerous females was recorded in the fall and winter. Mature gonads were found throughout the year and recruitment was continuous but more intense during the summer. The fecundity of N. granulata (30028.3 ± 10861.2 eggs) was high in comparison to studies in other localities. In general, the proportion of males was similar to that of females (1:0.92); however, males were predominant in the fall (1:0.77) and winter (1:0.75). All the information available so far on the reproduction of N. granulata involves populations from subtropical salt marshes; therefore, comparative studies including other habitats, such as mangrove forests, are needed to further understand the environmental influences on the population and reproductive biology of semiterrestrial crabs.
Keywords: Grapsoidea; population structure; semiterrestrial crab